The development and validation of a character education model through traditional games based on the Socratic method in an elementary school - Anne Hafina; Lutfi Nur; Arief Abdul Malik (Jurnal Cakrawala Pendidikan, 2022)
This study intended to build a character education model in an elementary school using traditional games based on the Socratic Method. This study used design-based research (DBR), with five experts helping to validate the character education model using a model evaluation instrument and 26 students participating in the model trial. As a result, the developed model comprises six elements: focus, syntax, reaction principles, social system, support system, and application. Meanwhile, the syntax, which consists of four steps: the initial stage, the transition stage, the working stage, and the termination stage, is the core of this model. Experts strongly agree that the model is in the "highly appropriate" category for fostering character development in elementary school students. There is a Socratic method in the developed syntax that encourages students to analyze the characters they encounter in traditional games. The study concludes that the proposed model can help students build character in elementary schools. Furthermore, this model can introduce and revive traditional games in Indonesia as part of the country's cultural heritage.